Penghindaran Pajak dan Risiko Kejatuhan Harga Saham: Tata Kelola Perusahaan Sebagai Variabel Moderasi - Eunike Apriella Wijono; Yie Ke Feliana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the relationship between tax avoidance and the stock price crash risk as well as the moderating effect as a mechanism of good corporate governance. This study uses a sample of listed companies on the IDX for the 2021-2022 by using panel data regression. This research is motivated by the opportunistic behavior of managers in hoarding negative information that accumulates and causes the risk of falling stock prices in the future. The results of this study found that there is a positive relationship between tax avoidance and the risk of stock price crashes when using the TA model and firm size with firm sigma as a dividing variable or firm sigma that is not more than average. The corporate governance mechanism also has an insignificant moderating impact on that relationship. This study presents ideas and contributions to the relationship between tax avoidance and the risk of stock price crashes with the moderating effect of corporate governance in Indonesia